Author Response: Reationship Between Headache Characteristics and a Remote History of TBI in Veterans: A 10-Year Retrospective Chart Review. (15th November 2022) - Androulakis, X. Michelle; Moore, R. Davis
Abstract : We appreciate Dr. Gupta's comments on our article, 1 but respectfully disagree. Our findings indicate clinicians may achieve a more precise prognosis of traumatic brain injury (TBI)–related headaches by eliciting a detailed history of TBI frequency and severity (subconcussive, mild, or moderate), loss of consciousness duration, alterations of consciousness, and posttraumatic amnesia as semicontinuous variables rather than categorical criteria. Not all headache occurrences had migraine-like features in veterans with TBI in this study.